BERGABUNGNYA KEMBALI AS DALAM KESEPAKATAN NUKLIR IRAN JCPOA (Perbedaan Kepemimpinan antara Presiden Trump dan Presiden Biden) Tahun 2022 - Rizky, Kiky; Sihabudin, Fryadiva Meshia (Emerald: Journal of Economics and Social Sciences, 2023)
The JCPOA (Joint Comprehensive Plan of Action) agreement, also known as the Iranian nuclear agreement, was officially agreed in 2015 in Vienna, Austria and signed by Iran with the Permanent Member States of the UN Security Council plus Germany and the EU. In contrast to his predecessor, in 2018 President Donald Trump declared that the United States was leaving JCPOA membership. This action drew public criticism and was deemed inappropriate in relation to the impact of Iran's increasing nuclear weapons development activities. So, Joe Biden in the 2020 general election campaign stated that he would restore the United States' membership with the Iran nuclear deal if elected. The purpose of this research is to find out the impact of Trump's decision to release the United States from membership in the JCPOA, how important the presence of the JCPOA is to maintain international nuclear peace, how Biden's efforts to restore the conflict between the United States and Iran, analyze the differences in the leadership styles of the two presidents from different parties. The research method used in this paper is a literature study by examining various journals, scientific papers, and the latest news on the United States presidency.